Seismic Performance Levels of a Large Underground Subway Station in Different Soil Foundations - Zhuang, Haiyang; Ren, Jiawei; Miao, Yu; Jing, Liguo; Yao, Erlei; Xu, Changjie (Journal of earthquake engineering : JEE, 2021)
With the soil constitutive model developed for the dynamic large deformation of soft soil, a finite element model was constructed to simulate the soil-underground structure static and dynamic coupling interaction system, in which the dynamic contact between soil and underground structure and the dynamic damage of reinforced concrete were considered. The seismic performance and damage mechanism of the large underground subway station in different soil foundations were investigated and evaluated in detail. It was proven that the interaction mechanism between the soil and underground structure would change with the type of soil foundation and the peak acceleration of input ground motion, which can be evaluated by the interaction coefficient between the soils and underground structure. At the same time, some regulations on the seismic performance of underground structure in China code are already unsuitable for evaluating the seismic performance of a large underground subway station in the soft soil foundation or subjected to a strong earthquake, which should be investigate by the specialized time-history analysis method instead. In this study, five seismic performance levels were firstly defined by the inter-storey drift angle of underground structure and corresponding earthquake damage states.